A frente ampla de oposição ao regime militar (1966-1968) - Marcio de Paiva Delgado (2013)
In the years after the 1964 Civil-Military Coup, many of the most important political leaders formed in the period known an Democratic Experience (1945-1964) either were exiled (João Goulart, Leonel Brizola and Miguel Arraes) or annulled (Juscelino Kubistschek, Luis Carlos Prestes, Henrique Teixeira Lott, Adhemar de Barros and Jânio Quadros). It was only Carlos Lacerda, ex-partner on the Coup and the main current civil leader of UDN (National Democratic Union), who raised as an opposing civil leader in the early years of Castello Brancos government, especially after the prorogation of the Presidential term and the AI-2 enactment. While the working-class, the communists and the Juscelinos political group started the conversations to organize an opposition to the dictatorship during the 1966s, Lacerda and Kubitschek, through his dealers, worked on agreements towards the process to redemocratize the country. From this moment on, Lacerdas and Juscelinos groups, some working-class members and some communists sided to Luis Carlos Prestes tried to carry out an opposing front, which was officially born in the Manifest of the Broad Front, on October 1966. In November, Lacerda and Kubitschek set an alliance and unveiled the Lisbon Declaration. In the following year, Lacerda and Goulart were connected in a polemic alliance as it was unveiled the Montevideo Pact on September 1967. Even though it was quite heterogeneous, the Broad Front had no antirevolutionary bias and it was very distant the opposing forces of the guerilla party or the student body. Along with Goularts term beginning and from the early 1968, the Broad Front stimulated a period of higher mobilization, with political rally and public acts, strengthened by a radicalization on the street movements, mainly the students ones. However, on April 5th 1968, in the midst of protests against the death of the student Edson Luis, the Minister of Justice published the administrative rule number 177, which prohibited the Broad Front actions and which considered illegal any manifestation under its name. The following months would reveal the total closure up to the AI-5 settlement and the annulment of all members of the Broad Front, including Carlos Lacerda. In this work, it will be show the historical trajectory of the Broad Front, in a narrative mood, under the perspective of the Political Cultures from this period, pointing out the gradual process of the Military system closure and the low engagement of Brazilian society both in its right and in its new left flag with the representative democracy in the pre-1964 era.